DevOps adoption in Junior Enterprise: an experience report of software development - Rodrigues, Peterson; Macedo, Juliano; França, Pedro; Franz, Luiz Paulo; da Silva, João Pablo; Cheiran, Jean (Anais da Escola Regional de Engenharia de Software (ERES), 2017)
Adopting new approaches to increase software development success rate in junior enterprise context is a constant challenge for this kind of company. In this paper, we report the experience on adoption of DevOps foundations to integrate continuous delivery in software development process. This adoption had three main moments: company diagnosis of maturity, application of tools to reach DevOps maturity level, and analysis of benefits of integration through one project in the company. Results indicate better transparency in project sta- tus through interactive communication provided by unifying development and operation areas, and faster software delivery.